Spectral Efficiency and Hybrid Multi-RSU Deployment with Cost Optimisation in Vehicular Ad Hoc Networks - Hamdi, Mustafa Maad; Rashid, Sami Abduljabbar; Nafea, Ahmed Adil; Audah, Lukman (Al-Khwarizmi Engineering Journal, 2026)
Enhanced traffic management and safety can be achieved using decentralised networks such as Vehicular Ad Hoc Networks (VANETs), which allow communication amongst vehicles. These networks support dynamic, real-time communications; however, they face difficulties in terms of scalability, security and network stability. Improved vision efficiency, cost reduction and enhanced connectivity in VANETs can be realised using multi-RSU and clustering methods, revealing real-world benefits. This research seeks to improve communication efficiency in VANETs by addressing issues such as network delay, power usage and communication cost. The goal is to improve network reliability in a dynamic vehicular setup with fixed Roadside Units (RSUs), ensuring constant connectivity and reduced overhead. Spectral Efficiency and Hybrid Multi-RSU Deployment with Cost Optimisation (SEHMR) approach introduces an innovative solution for improving vehicular communication. The system integrates clustering, scheduling and continuous cluster maintenance of vehicles. By analysing the initial population and probability values of vehicles, the Cost Optimisation (DEA) algorithm effectively optimises costs. RSUs are strategically positioned to improve coverage, communication and power efficiency. This approach is evaluated through extensive simulations using NS2 and the SUMO mobility suite, measuring performance through metrics such as efficiency, throughput, packet delivery ratio, data loss, end-to-end delay and overhead. The proposed SEHMR-VANET is compared with basic approaches such as HGAR-VANETS, ROOP-VANET and ISFF-VANETs. Results indicate that SEHMR-VANET achieves higher energy efficiency and lower delay and data loss, revealing its effectiveness in improving traffic communication.